THE ROLE OF WORKING CLASS (OTHER WOMEN) IN CRITICAL EDUCATION - Barbara Merrill (Ediciones Universidad de Salamanca, 2009)
This article looks at the role and experiences of working class (other) women who return to education in universities and community education. The educational experiences are explored through the voices of working class women by using feminist biographical approaches. The stories reveal the centrality of class and gender inequalities in the women's lives. The biographies highlight the potential of education as a transforming experience for working class women as they critically reflect upon their life experiences shaped by class and gender. The theoretical framework draws on feminism and radical women's education while critiquing academic feminism and arguing for a more dialogical approach. Although universities do offer a space for transformation for women the curriculum needs to draw more overtly on the experiences and knowledge of 'women adult students from below'.